On uniqueness theorems for holomorphic curves sharing hypersurfaces without counting multiplicity - Phuong, Ha Tran (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We prove some uniqueness theorems for algebraically nondegenerate holomorphic curves sharing hyper-surfaces ignoring multiplicity.